(5-3х)(1-х)>1
3x^2-8x+5>1
D=-8^2-4*3*4=16 v(D)=4
x1=(8-4)/(2*3)=2/3
x2=(8+4)/(2*3)=2
x1 = 2/3; x2 = 2
ответ (-∞;2/3)∪(2;+∞)
ответ:
d=b^2-4ac=(-1)^2-4*1*(-72)=1+288=\sqrt{289}
289
=17
х1=\frac{-b- \sqrt{d} }{2a} = \frac{1-17}{2} = \frac{-16}{2} =-8
2a
−b−
d
=
2
1−17
=
2
−16
=−8
х2=\frac{-b+ \sqrt{d} }{2a} = \frac{1+17}{2} = \frac{18}{2} = 9
2a
−b+
d
=
2
1+17
=
2
18
=9
ответ: -8 и 9
d=b^2-4ac=7^2-4*(-4)*(-3)=49-48=\sqrt{1} =1
1
=1
х1=\frac{-b- \sqrt{d} }{2a} = \frac{-7-1}{2*(-4)} = \frac{-8}{-8} =1
2a
−b−
d
=
2∗(−4)
−7−1
=
−8
−8
=1
х2=\frac{-b+ \sqrt{d} }{2a} = \frac{-7+1}{(-8)} = \frac{-6}{-8} =0,75
2a
−b+
d
=
(−8)
−7+1
=
−8
−6
=0,75
(5-3х)(1-х)>1
5-3x*1-x>1
-3x-x>-5+1
-2x>-4 |: (-2)
x<2
\
2
ответ: х принадлежит от [-бесконечности; до 2]